Innovative Communications Simulator in a Human Park and Vocational Development - TIWARI, DR. ARCHANA (The journal of contemporary issues in business and government, 2021)
Park for individual and economic growth is an umbrella for the Social Network for Personal and Career Advancement as part of a potential non-formal eco-entrepreneurship university. Innovative contact simulator with the focus on the excitement of the participants is for: completion of grade management to achieve the project website performance, contains www.recadd.ro guide; evaluating website development; providing feedback on potential alternatives and improving website. Using the EFI ROM method, the following ideas with practical applicability were obtained: use clubs to create project teams that are able to integrate more mature into the wider community; Create a Park for Community Growth and Personal Advancement through the Adaptability Clubs Network for Economic Progress; collaborate with friends; promote the sharing of shared experience; use conventional online practices.